Correction: Corrigendum: Agrp neuron activity is required for alcohol-induced overeating - Sarah Cains (Nature Portfolio, 2017)
Nature Communications 8: Article number: 14014 (2017); Published 10 January 2017; Updated 19 May 2017 The original version of this Article contained an error in the email address of the corresponding author Sarah Cains. The correct email is cains@hotmail.co.uk. The error has been corrected in the HTML and PDF versions of the Article.